The equation defined by y = x2 - 6x, means that if we are given a value for x (such as 0, 1, 2, 3, etc.), then we can find a y value by plugging in the x into the equation and doing the necessary operations.
When x = 0 the equation is y = (0)2 - 6(0) = 0, thus when x is 0, y is also 0. The coordinate...

When we are given an equation we can change its form by doing identical operations on both sides of the operation. So if we are given the equation 9/6 = x10 we can divide both sides of the equation by 10. Thus we get 9/6 divided by 10 = x10 divided by 10. The left side of the equation simplifies...

We know that the amount of quarters that Charlie has is x.
We know that the amount of quarters that Ty has is 3 more times as Charlie. Thus Ty has (x + 3) quarters.
We know that the amount of quarters that Vinnie has is 2 more times as Ty. Thus Vinnie has 2(x + 3) quarters, or 2x...

The equation we are working with is y = -x - 4
This equation is in slope-intercept form (y = mx + b), and m = -1 and b = -4. This means that the slope is -1 and that the y-intercept is -4. Thus, we know that the line is downward sloping, which means that it looks more like a backslash (\)...

A fraction with a negative sign in front of it is the same as a fraction with a negative sign in front of the numerator, or a fraction with a negative sign in front of the denominator.
For example:
-(1/2) = (-1)/2 = 1/(-2)
This is true because a negative one can be factored out from...

The information that is given is: f(x, y, z)=(z^2+x^2-y)/(2x^2+y) AND f(x, -x^2, x^2). This is saying that f is a function that is dependent on variables x, y, and z and is defined as (z2
+ x2 - y)/(2x2 + y). Furthermore the variables y and z are defined in terms of the variable...

x-2 - 1/x - 1 ______ given
= (1/x2) - (1/x) - (1) ______ x-2 can be written as 1/x2 and use parentheses to separate each term
= (1/x2) - (x/x2) - (x2/x2) ______ LCD is x2
= (1-x-x2)/(x2) ______ combine terms into single fraction
= (-x2-x+1)/(x2) ______ rearrange terms in...